When do international human capital enhancing practices benefit the bottom line? An ability, motivation, and opportunity perspective - Kim, Kyoung Yong; Pathak, Seemantini; Werner, Steve (Journal of International Business Studies, 2015)
We study the conditions under which firms can capitalize on their international human capital (IHC). Using the ability–motivation–opportunity (AMO) perspective we conceptualize IHC as ability, collaborative climate as motivation, and the firm’s level of internationalization as opportunity. We test three alternative AMO models – the additive model (main effect), the combinative model (two-way interactions), and the multiplicative model (a three-way interaction). Using a cross-industry sample of South Korean firms, we find support for the multiplicative model. Specifically, the relationship between IHC enhancement practices and firm performance is significant and positive only when both collaborative climate and internationalization are high.